Diphascon (Diphascon) dolomiticum, a new species of Hypsibiidae (Eutardigrada) from Italy - Pilato, Giovanni; Bertolani, Roberto (Zootaxa, 2005)
A new species of eutardigrade, Diphascon (Diphascon) dolomiticum sp. n., is described. It has three macroplacoids and microplacoid; claws short and stout; hind legs with basal margin indented; internal and external claws on the first three pairs of legs almost of the same length; anterior claws on the hind legs longer than the posterior claws.